Benefits realisation management: Social impact analysis - Pereira, L. (2023)
Social impact assessment and benefits management is commonly measured in social communities’ intervention plans. Although, its combined use lacks from a methodology or framework, which can assist in measuring those benefits and impacts. To achieve this, a business case tool has been applied in order to measure the benefits and Social Toolkit has been developed to assist the social impact. The results of these measures provided a substantial increment in terms of benefits measurements and social impact assessment in the social impact assessment of the ‘community intervention of proximity’ initiative, which aims to support families affected by poverty and/or victims of social exclusion. The results have shown that there has been a decrease in social exclusion and a reduction in poverty for needy families.